Venturing beyond donor-controlled glycosylation : new perspectives toward anomeric selectivity - Leng, Wei-Lin (2020)
Glycans are complex compounds consisting of sugars linked glycosidically, existing either as pure polysaccharides or as part of glycoconjugates. They are prevalent in nature and possess important functions in regulating biological pathways. However, their diversity coupled with physiochemical similarities makes it challenging to isolate them in large quantities for biochemical studies, hence hampering progress in glycobiology and glycomedicine. Glycochemistry presents an alternative strategy to obtain pure glycan compounds through artificial synthetic methods. Efforts in glycochemistry have been centered on glycosylation, the key reaction in glycochemistry, especially with regards to anomeric stereoselectivity in polysaccharides and glycoconjugates. In particular, the stereoelectronic and steric properties of glycosyl donors are commonly used to direct the stereoselectivity in glycosylation reactions. Classic glycosylation strategies typically involve saturated glycosyl donors, proceeding either directly using hydrogen bonds and conformational constraints or indirectly by installing moieties covalently through neighboring group participation and intramolecular aglycon delivery. Over the past years, new glycosylation strategies, tapping on the foundations of transition metal catalysis, have emerged. To leverage the power of coordination chemistry, unsaturated glycosyl donors were introduced. Not only are the number of protection/deprotection steps reduced, the resultant unsaturated glycoside provides opportunities for downstream functionalizations, allowing quick access to a variety of sugars, including rare sugars. Alongside the glycosyl donor, an equally important but neglected aspect for targeting stereoselective glycosylation is the glycosyl acceptor. In the case of dual-directing donors, glycosyl acceptors have proved themselves capable of becoming the dominating factor for stereocontrol. Interestingly, rational manipulation or selection of glycosyl acceptors with particular nucleophilicity and p Ka values can lead to different stereoselectivities, thereby proving the tunability of such acceptors to favor the formation of one anomer over the other stereoselectively. By further venturing beyond substrate controlled stereoselectivity, we are presented with the opportunity to effect stereoselective glycosylation through glycosylating reagents. Of the key reagents, stereoselective catalyst stands out as a greener and efficient alternative to direct stereoselective control with stoichiometric substrates. Recently, investigations into this approach of stereocontrol presented an intriguing range of stereoselectivities, achieved by merely varying the nature of catalysts used. Another crucial effort in glycochemistry is enhancing the efficiencies of glycosylations, by reducing the number of preparative steps before or during glycosylation. Through using transient masking groups or one-pot synthetic strategies, these streamlined approaches provide enormous convenience and practicability for oligosaccharide syntheses. This Account presents mainly our advancements beyond the conventional donor-controlled strategies over the past decade, with emphasis placed on mechanistic explanations of anomeric selectivities, thereby providing perspectives to inspire further progress toward a generalized unified strategy for preparing every type of glycan.